THE EFFECT OF LIGHT MASSAGE ON PERIFERAL BLOOD CIRCULATION IN TUBERCULOSIS PATIENTS - Sidik Awaludin; Annas Sumeru; Galih Noor Alivian; Arif Imam Hidayat (Universitas Muhammadiyah Kalimantan Timur, 2020)
ABSTRACT Tuberculosis is still a major problem in the health sector, including side effects from treatment Side effects from tuberculosis treatment that are often experienced include indigestion, nausea, joint pain, dizziness, redness, itching, redness of the skin, liver disorders, joint pain and paresthesia or tingling. Tingling caused by blood circulation is not smooth. Light massage is a massage therapy in the form of gentle movements on the soft tissues of the body including wiping and rubbing movements, this skin stimulus will provide a sense of comfort, relaxes tension in the muscles and increases blood circulation. The purpose of this study was to determine the effect of Light Massage therapy on peripheral blood circulation in tuberculosis patients. This study uses a true experiment pre and post control group design. The number of samples of this study were 30 respondents in the intervention group and 30 respondents in the control group. The study was conducted in the working area of ​​the Sokaraja Community Health Center. The sampling technique used is simple random sampling. The mean respondent was female (56.7%), with an intensive treatment phase (76.7%), mean Ankle Brachial Index (ABI) score in the intervention group 1.03 and the control group 1.06. There were no differences in ABI scores between the intervention and control groups. Administration of light massages interventions for 3 times has not been able to reduce the ankle brachial index score in tuberculosis patients. Further research needs to be done on ABI scores in patients with advanced treatment phases.